Transitioning from Solo Self-Employed to Microbusiness Employer: Local Economic Environment or Owner Characteristics? - Andrew Henley (Institute of Labor Economics (IZA), 2019)
Only a minority of micro-businesses create jobs for others. This paper addresses whether personal characteristics and resources of the microbusiness owner or the local external economic environment are drivers of job creation. In the UK context of significant growth in self-employment but a declining proportion who create jobs, an investigation using longitudinal data is provided. Individual demographic and resource characteristics are found to be more important, but place effects are relatively weak. Entrepreneurship policy needs to target particular groups, including women and less experienced business owners in their localities.
Keywords: J23; L26; M13; R12; 330; self-employment; micro-business; job creation; local environment; longitudinal analysis